AI-Powered Platforms for Protecting Women’s Rights and Transforming Widowhood Practices in Southern Nigeria - Tosin Olusola Ayedun; Oluwaseyi Abiodun Akpor; Elizabeth Funmilayo Ojo; Ifeoluwa Olubiyi; Adeniran Sunday Afolalu (ABUAD Journal of Engineering Research and Development)
Recently, there is an increasing attention of the media and other organisations on Women Rights violation and several myriad social challenges faced by vulnerable women in the Southern Nigeria. Thus, the study seeks to review these challenges and how the adoption of AI platforms can help to accelerate the protection of women Rights and the practice of widowhood in Southern Nigeria. Findings shows that there must be identification of the fundamental Rights and the women which are vulnerable in this area especially the widows. However, it was established that adoption of AI-platforms to help these women could also have impact on their Rights and protection. Hence, impact assessment is necessary to understand the level of risk associated with the usage of the tool. But most importantly, AI-powered solutions will help in enhancing their lifestyles and sustainable living if adequately deployed and monitored.